Single oral dose study of two isosorbide-based aspirin prodrugs in the dog - RYDER, SHEILA (My University, 2003)
The objective of this study was to compare two aspirin prodrugs, isosorbide diaspirinate (ISDA) and a nitroaspirin (ISMNA), with aspirin in terms of effects on dog platelet function after administration of a single oral dose. Groups of six dogs were administered ISDA (2 mg kg?1), ISMNA (4 mg kg?1) or aspirin (2 mg kg?1). Blood was sampled at 1, 2, 4, 8, 12 and 24 h post-dosing and evaluated for capacity to generate post-clotting thromboxane (TX)B2. The aggregation response to arachidonic acid (AA) (100 ?M), ADP (30 ?M) or collagen (10 ?g mL?1) was estimated at each time-point using the whole blood impedance method. Plasma ISMN following oral administration of ISMNA was also measured and compared with plasma ISMN following administration of a physical mixture of ISMN and aspirin. ISDA administration (2 mg kg?1) was associated with a significant reduction (P< 0.05) in serum TXB2 at 12 and 24 h (>90%) post-dosing and persistent inhibition of AA-induced platelet aggregation. ISDA administration caused a more marked depression of post-clotting TXB2 levels than aspirin in this study, although its ability to inhibit platelet aggregation was less consistent than that of aspirin. The nitroaspirin ISMNA was least effective at inhibiting platelet aggregation response or TXB2 production. The ISMN AUC0?24h for the ISMNA-treated dogs was 77% of that for the physical mix-treated dogs and the tmax was delayed. This study indicates that the two aspirin esters cause aspirin-like effects on platelet function, probably through aspirin release, when administered orally to dogs.
PUBLISHED
PMID: 14607016
Keywords: isosorbide; aspirin; prodrug; dog; nitroaspirin; platelet aggregation; acetylsalicylic acid; Aspirin; Blood platelets--Aggregation; acetylsalicylic acid; Drug development; Pharmacokinetics